2016
DOI: 10.24002/modus.v26i1.576
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Perencanaan Pajak Terhadap Manajemen Laba Pada Perusahaan Nonmanufaktur Yang Terdaftar Di Bursa Efek Indonesia

Abstract: This study aim to assess and obtain empirical evidence about the effect of tax planning on earnings management practices seteleh the change (decrease) PENDAHULUANManajemen laba merupakan upaya yang dilakukan pihak manajemen untuk melakukan intervensi dalam penyusunan laporan keuangan dengan tujuan untuk menguntungkan dirinya sendiri, yaitu pihak perusahaan yang terkait. Manajemen laba dapat dilakukan melalui praktik perataan laba (income smoothing), taking a bath, dan income maximization (Scoot, 2000). Kons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
3
39

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 1 publication
4
19
3
39
Order By: Relevance
“…This may be due to more strict tax regulations, so the tax planning that made by the company less effective to minimize taxes in order to increase profits. The results of this study are consistent with Subagyo and Oktavia (2010), Ulfah (2013), Aditama and Purwaningsih (2013).…”
Section: Trr = Net Income It Ebit Itsupporting
confidence: 92%
See 2 more Smart Citations
“…This may be due to more strict tax regulations, so the tax planning that made by the company less effective to minimize taxes in order to increase profits. The results of this study are consistent with Subagyo and Oktavia (2010), Ulfah (2013), Aditama and Purwaningsih (2013).…”
Section: Trr = Net Income It Ebit Itsupporting
confidence: 92%
“…The political cost hypothesis in a positive accounting theory states that the company is trying to avoid large political costs, for example the tax burden, the higher tax value, the lower the profits to be obtained. Research Subagyo and Oktavia (2010), Ulfah (2013), Aditama and Purwaningsih (2013), concluded that tax planning has a significant positive effect on earnings management. Based on the above, the hypothesis is formulated as follows H5:Tax Planning has positive effect on earnings management practices…”
Section: Tax Planning and Earnings Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Earnings thresholds are classified into two,: (1) Zero earnings report indicating earnings management efforts to avoid losses reporting; and (2) Zero earnings changes has indicated the efforts of earnings management to avoid profits decrease. (Aditama and Purwaningsih, 2014).…”
Section: B Earnings Managementmentioning
confidence: 99%
“…Penelitian yang dilakukan (Dechow & Skinner, 2000) menyatakan bahwa terdapat perbedaan pandangan atas manajemen laba terhadap kelompok akademis, praktisi dan regulator. Manajemen laba tidak dipengaruhi oleh perencanaan pajak (Aditama & Purwaningsih, 2014), (Yunila & Aryati, 2018). Sedangkan (Fitrany, 2016), (Negara & Saputra, 2017), (Sumomba & Hutomo, 2012), (Widiastuti & Chusniah, 2011) yang berpendapat bahawa perencanaan pajak memiliki pengaruh terhadap manajemen laba.…”
unclassified